2017
DOI: 10.12968/bjon.2017.26.16.932
|View full text |Cite
|
Sign up to set email alerts
|

Research into experiential learning in nurse education

Abstract: This research is founded on an innovative pedagogical project as part of a higher education lecturer teaching qualification. This project involved redesigning the module 'advanced history taking and physical examination with clinical reasoning', a continuing professional development at a higher education institution. The author undertook an exploration of the literature, considering evidence on teaching styles and the way in which students learn and gain knowledge. The module was redesigned, impelemented and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 15 publications
1
47
0
1
Order By: Relevance
“…Most staff had not tasted thickened fluids before and doing so may have helped them to understand, and ultimately empathise, with this aspect of the resident experience. This demonstrates the importance of providing experiential modes of training (Hill, 2017), not commonly applied in the care home environment, when attempting to enhance learning and promote change in competence and practice.…”
Section: Discussionmentioning
confidence: 99%
“…Most staff had not tasted thickened fluids before and doing so may have helped them to understand, and ultimately empathise, with this aspect of the resident experience. This demonstrates the importance of providing experiential modes of training (Hill, 2017), not commonly applied in the care home environment, when attempting to enhance learning and promote change in competence and practice.…”
Section: Discussionmentioning
confidence: 99%
“…A learning environment focusing on patient-centered education seems to improve both deep and active learning as well as IM [ 17 ]. There are also reports that the students adopted deep learning during experiential education [ 19 , 20 ]. These findings suggest that clinical clerkship can help to develop deep learning process and improve the learning motivation of pharmacy students.…”
Section: Discussionmentioning
confidence: 99%
“…A. Kolb, 1984). Both aeronautical and medical disciplines have strong histories of experiential education incorporating simulation, and although much research has been reported on the role of simulation in aeronautical and medical education, specific research could only be found linking Kolb's experiential learning theory in nursing programs (Bell & Waag, 1998;Caro, 1977;Carron, Trueb, & Yersin, 2011;Connolly, Blackwell, & Lester, 1989;Dahlstrom, 2008;Hill, 2017;Labrucherie, 2016;Lisko & O'Dell, 2010;Qayumi et al, 2014).…”
Section: Perspectives and Applicationmentioning
confidence: 99%
“…Efforts to apply Kolb's theory to one university's nursing curriculum involved incorporating simulated scenario-based critical skills integration exercises to facilitate critical thinking as well as to accommodate individual learning styles (Hill, 2017;Lisko & O'Dell, 2010). Kolb's experiential learning theory addresses the importance of learning experiences and the theory's multiple components affords various types of learners to be successful by "creating knowledge by transforming experience into cognitive frameworks, thus changing the way a person thinks and behaves" (Kolb, 1984, p. 106).…”
Section: Perspectives and Applicationmentioning
confidence: 99%
See 1 more Smart Citation